OCCURRENCE OF PANULIRUS LONGIPES LONGIPES, PANULIRUS PENICILLATUS AND PANULIRUS POL YPHAGUS IN THi: GULF OF MANNAR WITH NOTES ON THE LOBSTER FISHERY AROUND MANDAPAM - Nair, R V; Soundararajan, R; Dorairaj, K (Indian Journal of Fisheries, 2011)
In a recent revision of the Indo-West pacific spiny lobsters of the genusPanulirus, George and Holthuis (1965) have recognised eleven species, they beingPanulirus homarus (L), P. orruitus (Fabricius), P. polyphagus (Herbst), P. versicolor(Latreille), P. penicillatus (Olivier), P. longipes (A. Milne Edwards), P. Japonicus(Van Siebold), P. pascuensis Reed, P. marginatus (Quoy and Oaimard), P. cygrusGeorge and P. stimpsoni Holthuis of which the first six species alone have so farbeen recorded from Ihe Indian Waters (Alcock 1901, Gravely 1927, Rai 1933, Chopra1939, Miyamoto and Shariflf 1961, Balasubramanian et al 1960, Satyanarayana 1961,George 1965, George and Rao 1965 and Prasad and Tampi 1968).